Information seeking behavior of forensic experts in selected investigating institutions in Metro Manila - Gutierrez, Harriette Josephine B.; Cabbab, Johann Frederick A.; Philippine National Police; National Bureau of Investigation (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
This study focused on the information seeking behavior of forensic experts in selected Investigatory Institution in Metro Manila. This study aimed to find out the searching strategies of forensic experts; the types of materials forensic experts prefer to use in searching and as to format; the feelings, behaviors and thoughts they have during the search process, and the issues and concerns of forensic experts in information seeking process.
The research methodologies used were the survey method and interview schedule. One hundred thirty (130) questionnaires were distributed out of which 88 were returned. Informal interview was conducted for clarifications and elaboration to some of the forensic experts' answers in the questionnaire, and it aimed to verify the researcher's hypotheses to the study.
The results of the study showed that forensic experts have different ways of keeping themselves updated of the recent developments in their field. Most of them do it through scanning of the current issues on print journals and through the use of Internet/E-mail alerts. They heavily rely on primary authority materials. They use secondary authority to gain additional information and find other explanations. Since there is a lack of materials in both offices, forensic experts are not very much concerned whether they use primary sources or secondary sources, as long as they find the information they need. Based on the findings of the study, it is also concluded that not all forensic experts are knowledgeable of the usage of all the forensic materials.
The thoughts and feelings that Kulthau mentioned to accompany the information seeking process are also found to be true in forensic experts. It is found out that most of forensic experts are confident, enthusiastic, proud and optimistic when given a topic to research. When they are able to find what they need, they usually feel proud, confident, satisfied, and relieved. However, they feel disappointed and frustrated when they are unable to find what they were looking for.
The results of the study also revealed that they are also concerned with time constraints since they handle Tool many cases and investigations in and out of the office that sometimes causes delays to them in searching for information.
The major concerns of forensic experts are greatly concerned with time and the availability of materials.
After the analysis has been sought, the following recommendations were made: (1) Both offices should have a collection of forensic materials, since most of them heavily rely on their personal materials or reference that are useful for their forensic experts; (2) It is important for these offices to have their own collection of forensic materials to help forensic experts become more productive and to improve their services as well; (3) Librarians or information professionals in these two offices must learn strategic ways on how to market their library since there are still forensic experts who do not know that a library in their institution does exist; (4) The institution's librarians must also be given training on the usage and functions of the forensic materials so that they will be able to contribute to the forensics research process; (5) Finally, a study on evaluation of the library of the two offices must be conducted to suggest for new provision and be able to review their activities or plan of action for the improvement of their holdings and collection and also help forensic experts and other patrons of the library to strengthen their information searching process.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Forensic scientists -- Philippines -- Manila Metropolitan Area; Forensic scientists -- Information storage and retrieval systems -- Criminal investigation